2009
DOI: 10.1007/s10460-009-9191-z
|View full text |Cite
|
Sign up to set email alerts
|

Environment influences food access and resulting shopping and dietary behaviors among homeless Minnesotans living in food deserts

Abstract: Qualitative and quantitative methods were used to investigate how shopping behaviors and environment influence dietary intake and weight status among homeless Minnesotans living in food deserts. Seven focus groups (n = 53) and a quantitative survey (n = 255), using the social cognitive theory as the theoretical framework, were conducted at two homeless shelters (S1 and S2) in the Twin Cities area. Heights, weights, and 24-h dietary recalls were also collected. Food stores within a five-block radius of the shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…By contrast, the highest level of satisfaction with food-related life in Groups 1 and 3 may be associated with the greater support in tangible or economic resources that these students receive, including food, given that some studies have shown that spending more money on food is linked to the opportunity to gain access to better quality and healthier food. This has been found in samples of families with small children in Minnesota, USA (French et al 2010), homeless adults also living in Minnesota (Smith et al 2010), adults mainly in the USA (Giskes et al 2011) and adults from ethnic minorities (of Mapuche origin) in Chile (Schnettler et al 2012). Thus regarding Hypothesis 2, it can be stated that the tangible or economic resources that students receive is positively related to their satisfaction with food-related life and better eating habits, which is also connected to the socioeconomic level of the students' homes.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…By contrast, the highest level of satisfaction with food-related life in Groups 1 and 3 may be associated with the greater support in tangible or economic resources that these students receive, including food, given that some studies have shown that spending more money on food is linked to the opportunity to gain access to better quality and healthier food. This has been found in samples of families with small children in Minnesota, USA (French et al 2010), homeless adults also living in Minnesota (Smith et al 2010), adults mainly in the USA (Giskes et al 2011) and adults from ethnic minorities (of Mapuche origin) in Chile (Schnettler et al 2012). Thus regarding Hypothesis 2, it can be stated that the tangible or economic resources that students receive is positively related to their satisfaction with food-related life and better eating habits, which is also connected to the socioeconomic level of the students' homes.…”
Section: Discussionmentioning
confidence: 71%
“…Too little food creates discontent among people (Grunert et al 2007). Many studies indicate that the possibility of spending a higher amount on food for the home is associated with the possibility of gaining access to better quality and healthier food (French et al 2010;Smith et al 2010;Giskes et al 2011;Schnettler et al 2012). However, the ability to allocate more resources for food may not necessarily translate into healthier diets.…”
Section: Satisfaction With Life and Food-related Lifementioning
confidence: 99%
“…1 The inadequacies of the environment in low-income neighborhoods have been widely implicated as a mediating factor in the paradoxical association between poverty and obesity. 2,3 Lower-income neighborhoods are less likely to have large supermarkets in close proximity that offer high-quality, nutritious, and affordable food, [4][5][6] and convenience stores and restaurants are more plentiful. 7,8 In addition, fewer opportunities exist for engaging in physical activity in lowincome communities.…”
mentioning
confidence: 99%
“…12,15 Paradoxically, homeless people are as or more likely than other Americans to be overweight/obese. 16 In a study of homeless adults, Smith et al found that 59.4% were obese (body mass index [BMI]≥30) 17 compared to an obesity rate among all Americans of 33.8%. 18 Additionally, surveys have found that 46% to 54.8% of homeless persons report chronic health conditions, such as diabetes, anemia, obesity, and hypertension.…”
mentioning
confidence: 99%